Plant Defenses Against Pests Driven by a Bidirectional Promoter - Arnaiz, Ana; Martinez, Manuel; Gonzalez-Melendi, Pablo; Grbic, Vojislava; Diaz, Isabel; Santamaria, M. Estrella (Frontiers in Plant Science, 2019)
The plant defence responses to pests results in the synchronized change of a complex network of interconnected genes and signalling pathways. An essential part of this process is mediated by the binding of transcription factors to the specific responsive cis-elements within in the promoters of phytophagous-responsive genes. In this work, it is reported the identification and characterization of a bidirectional promoter that simultaneously co-regulate two divergent genes, At5g10300 and At5g10290, upon arthropod feeding. Computational analysis identified the presence of cis-elements within the intergenic region between two loci, mainly from the DOF but also from the AP2/ERF, Golden 2-like and bHLH families. The bidirectional promote-function was analysed using two enhanced variants of the GFP and CherryFP reporter genes, in both orientations, in transient tobacco and stably transformed Arabidopsis plants. Promoter activity was tested in response to feeding of Tetranychus urticae and Pieris brassicae, as well as wounding, flagellin and chitin treatments. Using RT-qPCR assays and confocal microscopy, it was shown that all treatments resulted in the induction of both reporter genes. Furthermore, our findings revealed the asymmetric character of the promoter with stronger activity in the forward than in the reverse orientation. This study provides an example of a bidirectional promoter with a strong potential to be used in plant biotechnology in the pest control that requires stacking of the defence genes.